Land‐sparing agriculture sustains higher levels of avian functional diversity than land sharing. (13th March 2019) - Cannon, Patrick G.; Gilroy, James J.; Tobias, Joseph A.; Anderson, Alex; Haugaasen, Torbjørn; Edwards, David P.
Abstract: The ecological impacts of meeting rising demands for food production can potentially be mitigated by two competing land‐use strategies: off‐setting natural habitats through intensification of existing farmland (land sparing), or elevating biodiversity within the agricultural matrix via the integration of "wildlife‐friendly" habitat features (land sharing). However, a key unanswered question is whether sparing or sharing farming would best conserve functional diversity, which can promote ecosystem stability and resilience to future land‐use change. Focusing on bird communities in tropical cloud forests of the Colombian Andes, we test the performance of each strategy in conserving functional diversity. We show that multiple components of avian functional diversity in farmland are positively related to the proximity and extent of natural forest. Using landscape and community simulations, we also show that land‐sparing agriculture conserves greater functional diversity and predicts higher abundance of species supplying key ecological functions than land sharing, with sharing becoming progressively inferior with increasing isolation from remnant forest. These results suggest low‐intensity agriculture is likely to conserve little functional diversity unless large blocks of adjacent natural habitat are protected, consistent with land sparing. To ensure the retention of functionally diverse ecosystems, we urgently need to implement mechanisms for increasing farmland productivity whilst protecting spared land. Abstract : Using landscape and community simulations, we test the performance of land‐sparing and land‐sharing cattle pasture in conserving avian functional diversity of the Colombian Andes. We show that land‐sparing agriculture conserves greater functional diversity and predicts higher abundance of species supplying key ecological functions than land sharing. To ensure the retention of functionally diverse ecosystems, we urgently need to implement mechanisms for increasing farmland productivity whilst protecting spared land.